2018
DOI: 10.3892/ol.2018.8905
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‑29a inhibits colon cancer growth by regulation of the PTEN/Akt/GSK3β and Wnt/β‑catenin signaling pathways

Abstract: Abstract. In the present study, the effects of microRNA-29a (miRNA-29a) on colon cancer cell viability and the molecular mechanisms underlying the effects were investigated. The expression of miRNA-29a in colon cancer serum samples was notably downregulated, compared with in the normal group. First, miRNA-29a mimic was used to increase the expression of miRNA-29a in HCT-116 cells. Furthermore, upregulation of miRNA-29a suppressed cell viability, increased lactate dehydrogenase levels and apoptosis, and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…β-catenin is not degraded and accumulates in the cytoplasm. Inhibition of the Wnt/β-catenin signaling pathway in colon cancer has been found to alleviate the degree of deterioration of colon cancer (4749). In the present study, with the activation of the Wnt/β-catenin signal pathway, the Wnt activator SB2617763 was found to reverse the inhibitory effect of siSTC2 on Wnt/β-catenin and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin is not degraded and accumulates in the cytoplasm. Inhibition of the Wnt/β-catenin signaling pathway in colon cancer has been found to alleviate the degree of deterioration of colon cancer (4749). In the present study, with the activation of the Wnt/β-catenin signal pathway, the Wnt activator SB2617763 was found to reverse the inhibitory effect of siSTC2 on Wnt/β-catenin and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological functions of miR-29a might be controversial. It has been shown that miR-29a downregulates the activity of Wnt/β-catenin signaling in colon cancer 32. In addition, the cytokines, including FZD3, FZD5, DVL3, FRAT2, and CK2A2, involved in Wnt/β-catenin signaling have been showed to be the potential targets of miR-29 in miR-29 gain- and loss-of-function microarray experiments in primary human articular chondrocytes 5.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-29a has previously been reported to promote hepatoma cell migration by directly targeting PTEN, a key regulator of migration in many cell types [17, 50]. We observed that miR-29a robustly downregulates PTEN in glioblastoma cells that have intact PTEN function.…”
Section: Discussionmentioning
confidence: 52%